2021
DOI: 10.1002/cjce.24097
|View full text |Cite
|
Sign up to set email alerts
|

Synergy mechanism for TiO2/activated carbon composite material: Photocatalytic degradation of methylene blue solution

Abstract: To improve the photocatalytic effect of TiO 2 and the possibility of recycling, three different types of commercial activated carbon (AC) are used to prepare the TiO 2 /AC composite photocatalyst using the sol-gel method. The properties and catalytic activity of TiO 2 /AC composite are evaluated in comparison with bare TiO 2 , based on several characterization techniques and methylene blue (MB) photodegradation studies. The results show that the addition of AC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…[50,54] The interaction effect of photocatalyst and PS concentrations at 250 mg/L of PMS is depicted in Figure 4. Similar to Figure 3, raising the photocatalyst and PS concentrations up to their optimum values improved the degradation efficiency; that can be attributed to the formation of radicals through reactions ( 8), ( 9), (22), and (23). [3,53] S…”
Section: Analysis Of Individual and Interaction Effects Of Parameterssupporting
confidence: 66%
See 1 more Smart Citation
“…[50,54] The interaction effect of photocatalyst and PS concentrations at 250 mg/L of PMS is depicted in Figure 4. Similar to Figure 3, raising the photocatalyst and PS concentrations up to their optimum values improved the degradation efficiency; that can be attributed to the formation of radicals through reactions ( 8), ( 9), (22), and (23). [3,53] S…”
Section: Analysis Of Individual and Interaction Effects Of Parameterssupporting
confidence: 66%
“…Several attempts have been made to enhance the photocatalytic activity of TiO 2. [22][23][24][25][26][27] The incorporation of oxidants such as persulphate (PS) and peroxymonosulphate (PMS) in the photocatalytic reaction is a promising method to accelerate the rate of degradation by creating more reactive and diverse species as well as decreasing the rate ofelectron-hole recombination. [28][29][30][31] Madhavan and coworkers found that PMS was more effective than PS to improve the degradation rate of acid red 88 in the presence of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalytic activity tests are utilized to further substantiate the ability of TiO 2 and ZnO to generate free radicals and the inhibitory effect of lignin on this ability. The contents of • OH and • O 2 − , both of which are the main reactants for photocatalytic MB degradation, 53,54 are positively correlated with the degradation rate. Figure 12c shows that the degradation rate of the modifier is 3T > 3Z ≫ 3T5L ≈ 3Z5L.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…(1) adsorption: AC was trapped and accumulated the benzene gas around the catalyst, which then transferred to the active site of TiO2 for the photo-degradation process [18], (2) AC could acidify the OH groups in the TiO2 surface, these could lead to extra degradation and complete removal of the pollutant, (3) AC could play a role in the oxidation step via the transfer of electron/hole and also the large AC pores can accelerate the flow of benzene to the photo-oxidative species [19], (4) in addition,…”
Section: Application Of Ac/tio2 Air Purifier Filter For Benzene Gas C...mentioning
confidence: 99%